A influência de adições de escória de alto-forno e ardósia finamente moídas nas propriedades dos concretos - Waldemar Vaz de Resende (2012)
The overall objective of this project was to analyze the behavior of concretes by additions of finely ground blast furnace slag and waste (scrap) of slate. To this end it was necessary to evaluate the behavior of concrete when subjected to the following additions variations: (1) the percentage of admixture with finely ground blast furnace slag; (2) the percentage of the mixture with finely ground blast furnace slag and slate. Variations analyses of specific areas of blast furnace slag by means of Blaines permeameter integrated the experimental procedures. Became relevant, too, evaluating the concrete properties in the laboratory on the compressive strength evaluated from ultrasound tests and on the dynamic and static modulus of elasticity. It was found that during experimental tests the results obtained at 3, 7 and 14 days already showed a possibility which was confirmed at 28 days, maintained and improved up to 63 days: the addition of blast furnace slag, which has been well-studied and whose results have been encouraging in terms of concrete resistance, have been improved and become more meaningful with the tailings of slate joint addition. The tailings of slate, which raises several issues to miners and industrials in terms of transport expenses, disposal and areas maintenance, had not yet been addressed. The completion of this experimental study is that slate added to the blast furnace slag and cement, as well as to the additive multipurpose footrest, in established dosages, provides improved resistance of concrete besides producing benefits for the environment, once it promotes the use of piles and piles of waste material which hitherto did not present any more noble technical-commercial use.